1999
DOI: 10.1002/(sici)1097-0010(199906)79:8<1081::aid-jsfa330>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

The influence of various phenolic compounds on scavenging activity assessed by an enzymatic method

Abstract: The effect of pure monomeric and dimeric procyanidins on superoxide anion radicals (O2°−) was studied with an enzymatic method and their IC50 was determined. A comparative study of the results suggested that the antiradical potential of these phenolic compounds closely depends on their stereochemical structure. Modification of the chiral carbon, C3 involved in the oxidation mechanism induces differences in the scavenging action of (+)‐catechin (2R : 3S) or (−)‐epicatechin (2R : 3R). The stereochemical conforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(35 citation statements)
references
References 11 publications
2
33
0
Order By: Relevance
“…The scavenging action of various phenolic compounds is closely connected with their spatial conformation. The epicatechin unit of phenol has been found to be more efficient than catechin (Gaulejac et al ., 1999). Similar results have been reported by Chu et al .…”
Section: Resultsmentioning
confidence: 88%
“…The scavenging action of various phenolic compounds is closely connected with their spatial conformation. The epicatechin unit of phenol has been found to be more efficient than catechin (Gaulejac et al ., 1999). Similar results have been reported by Chu et al .…”
Section: Resultsmentioning
confidence: 88%
“…In the present study enhanced phenolic content and antioxidant activity was observed in most samples, suggesting that these phenolics were antioxidant in nature. The increase could be due to phenolic aglycosylation (Hopia and Heinonen, 1999), phenolic polymerization (Oki et al, 2002), and/or phenolic oxidation (Gaulejac, Vivas, Freitas and Burgeois, 1999) which are some known causes. Increase in total antioxidant activity of the heat-processed sweet corn was explained to be due to increase in solubilized ferulic acid esters and increased release of bound phenolics from the cell matrix .…”
Section: Resultsmentioning
confidence: 99%
“…Thus the natural antioxidants present in foods and other biological materials have attracted considerable interest because of their presumed safety and potential nutritional and therapeutic eects (Steinberg, 1991;Ames et al, 1993). Foods rich in antioxidants have been shown to play an essential role in the prevention of cardiovascular diseases (Renaud & de Lorgeril, 1992;Fuhrman et al, 1995), cancers (Dragsted et al, 1993;Wargovich, 2000), neurodegenerative diseases, the most well known of which are Parkinson's and Ahlzeimer's diseases (Okuda et al, 1992;Clarke, 1999;Joseph et al, 1999), as well as in¯ammation (Lietty et al, 1976;Joseph et al, 1999) and problems caused by cell and cutaneous ageing (Ames et al, 1993;Gaulejac et al, 1999a;Prior & Cao, 2000).…”
Section: Antioxidantsmentioning
confidence: 99%
“…It is known that the degree of glycosylation signi®cantly aects the antioxidant properties of the compound, for example, aglycones of quercetin and myricetin were more active than their glycosides . The molecular scavenging mechanism of these molecules is closely related to their stereo chemical structure (Gaulejac et al, 1999a). Catechins and their epimers serve as powerful antioxidants for directly eliminating super oxide anion radicals.…”
Section: Polyphenolsmentioning
confidence: 99%